Exercise Intensities as Factors of Metabolic Outcomes in Type 2 Diabetes: A Systematic Review. Issue 3 (August 2019) - Moxley, Elizabeth; Bugaieski, Tory
Exercise is effective to prevent and treat type 2 diabetes, although currently underutilized. This review analyzes the metabolic response to exercise performance at various intensities in individuals with type 2 diabetes. These findings provide insight into the development of safe and efficacious exercise prescriptions and education. We conducted a systemic review of the literature to examine the association of various exercise protocols with metabolic outcomes in type 2 diabetes. Between 1984 and 2018, 29 studies were categorized per exercise mode and intensity levels according to the American College of Sports Medicine standards. The most consistent improvement was found in HbA1c following moderate- to high-intensity exercise—post-exercise fasting glucose improved to a lesser extent. Low-intensity exercise improved HOMA-IR (homeostasis model assessment for insulin resistance) levels. Glucose and HbA1c improved most following interval compared with continuous exercise, irrespective of intensity. A comparison of high-intensity exercise with moderate-intensity exercise demonstrated few differences in HbA1c, fasting glucose, fasting insulin, and HOMA-IR. Irrespective of exercise intensity, HbA1c improvements were observed, suggesting a delayed progression to diabetes-related complications. Initial low-intensity exercise, with increased quantities when feasible, will contribute to metabolic improvements. The variability in methodology and measurement contributed to inconsistent outcomes; additional research with larger samples sizes is warranted.